A Twitter-Based Economic Policy Uncertainty Index: Expert Opinion and Financial Market Dynamics in an Emerging Market Economy - Yeşiltaş, Sevcan; Şen, Anıl; Arslan, Beyza; Altuğ, Sumru (Frontiers in Physics, 2022)
In this paper, we construct a Twitter-based high-frequency Economic Policy Uncertainty (TEPU) index built on a select set of Twitter user accounts whose tweets are considered to reflect expert opinion on the topic. We study the relationship between the TEPU index and a key set of financial indicators for tracking financial developments in Turkey over the sample period 2013-2021. Based on the results from a vector autoregressive analysis, we find evidence that changes in expert opinion described by fluctuations in the TEPU index interact with fluctuations in financial indicators such as the exchange rate and the stock market index to capture information about high frequency events during our sample period. Second, fluctuations in the TEPU index emerge as a key indicator that helps to predict domestic assessments of the country risk premium measured by the CDS spread. We also find evidence that the conditional volatility of the different series reflects salient events that occurred over our sample period.